1985
DOI: 10.1016/0014-5793(85)80640-2
|View full text |Cite
|
Sign up to set email alerts
|

Introns, protein syntheses and aging

Abstract: In the fungus Podospora, a correlation has recently been established between the presence of circular DNA molecules arising from the mitochondrial genome (SEN-DNAs) and the senescence syndrome. Here, I propose a hypothesis which accounts for the initial event which leads to the first SEN-DNA. A molecule in the most frequent situation where the SEN-DNA is an intron which might code for a maturase. This hypothesis is based upon several observations made either in Podospora or in the yeast S. cerevisiae. It assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Either the intron has the property of excision at the DNA level, or the gene is processed by a DNA-DNA recombination event involving a reverse transcript of the mature messenger. The first hypothesis could imply intervention at the DNA level of an RNA maturase encoded by the intron ca (Picard-Bennoun, 1985). The second, postulated to explain the origin of pseudogenes in mammals (Wilde et al, 1982), implies that Podospora possesses a reverse transcriptase which could also be responsible for the synthesis of SEN-DNAca from the corresponding intronic RNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Either the intron has the property of excision at the DNA level, or the gene is processed by a DNA-DNA recombination event involving a reverse transcript of the mature messenger. The first hypothesis could imply intervention at the DNA level of an RNA maturase encoded by the intron ca (Picard-Bennoun, 1985). The second, postulated to explain the origin of pseudogenes in mammals (Wilde et al, 1982), implies that Podospora possesses a reverse transcriptase which could also be responsible for the synthesis of SEN-DNAca from the corresponding intronic RNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the error rate per se does not influence the senescence process. The way in which the cytosolic translational apparatus is involved is not clear (21,26). However, it has been reported that aging in Drosophila is associated with a sharp decline in the rate of synthesis of the translational elongation factor la (EFla) (27).…”
mentioning
confidence: 99%